Introduction to cognitive pragmatics - Panther, Klaus-Uwe, 1942- (Cognitive Linguistics in Practice Ser., 2022)
"This textbook is designed for advanced (graduate and postgraduate) students, and will also be of interest to scholars. It blends a cognitive linguistic approach to language and language use with insights from contemporary pragmatics, the ultimate aim being to advance a unified model of cognitive pragmatics. Basic themes in cognitive linguistics and pragmatics are covered ranging from figurative language and thought, e.g. conceptual metaphor and metonymy, the role of inferencing in the construction of meaning, in particular, indirect speech acts, to the conceptual and functional motivation of morphosyntactic structure. Finally, the book offers many suggestions and ideas for student papers as well as larger research projects that promise to reveal new insights into conceptual structure, communicative function, and their influence on the grammatical structure of language"--